2017
DOI: 10.1099/jmm.0.000468
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization of class 1 integrons in Escherichia coli from healthy individuals and those with urinary infection

Abstract: Purpose. Class 1 integrons are among the main vehicles that facilitate the spread of antibiotic-resistance genes, with serious public health consequences. The aim of this cross-sectional study was to investigate the presence of class 1 integrons and to characterize their variable regions, as well as the antimicrobial resistance profiles and phylogenetic groups of a collection of Escherichia coli isolates recovered from healthy subjects (n=42) and those with urinary infection (n=40).Methodology. The methods use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 42 publications
9
28
1
Order By: Relevance
“…The high frequency of MDR isolates in Kermanshah may be due to the dissemination of class I integrons in the bacteria. The correlation between MDR isolates and class I integrons has been previously reported (27). These findings emphasize the importance of integrons in the development of high resistant strains due to acquiring and expressing various resistance genes.…”
Section: Discussionsupporting
confidence: 69%
“…The high frequency of MDR isolates in Kermanshah may be due to the dissemination of class I integrons in the bacteria. The correlation between MDR isolates and class I integrons has been previously reported (27). These findings emphasize the importance of integrons in the development of high resistant strains due to acquiring and expressing various resistance genes.…”
Section: Discussionsupporting
confidence: 69%
“…The "integron effect" -observed also with MDR K. pneumoniae (see above) -may account for the circumstance. Class 1 integrons are common in E. coli (Copur-Cicek et al, 2014;Oliveira-Pinto et al, 2017) including ST131 isolates (Pérez-Etayo et al, 2018) and it is well-established that they are mostly associated with weak promoters (Vinué et al, 2011;Wei et al, 2013). It was demonstrated that these "weak-promoter integrons" are "low-cost structures" in E. coli and their carriage influences the fitness of the pathogen (Lacotte et al, 2017).…”
Section: The Virulence Component In Mdr E Colimentioning
confidence: 99%
“…Here we present the first comprehensive AMR phenotypic data and molecular characterization for multiple antimicrobials, detecting several common mobile elements mediating the AMR including small plasmids, class I integrons with different cassettes and transposons including Tn6029, Tn10 and Tn1721 ( Fig S3). Many of the common mobile elements we detected have been reported widely in E. coli and other Enterobacteriaceae from human intestinal and extra-intestinal and animal samples [32][33][34][35][36] . Thus, while not conducted for the specific purpose of AMR surveillance, these aEPEC are likely represent a holistic overview of E. coli, and possibly other Enterobacteriaceae, in circulation at the study sites.…”
Section: Discussionmentioning
confidence: 74%